Factors associated with multidrug-resistant organism (MDRO) mortality: an analysis from the national surveillance of multidrug-resistant organism, 2018-2022 - Sharifa Ezat WP; M Norhidayah; Muhammad Nur Amir AR (BMC Infectious Diseases)
Abstract Introduction Antimicrobial resistance is a global issue, with the World Health Organization identifying it as one of the greatest threats to public health, with an estimated 4.95 million deaths linked to bacterial AMR in 2019. Our study aimed to determine the prevalence of mortality among multidrug-resistant organism (MDRO)-infected patients in state hospitals and major specialist hospitals and to identify risk factors that could be associated with mortality outcomes. Methods This is a cross-sectional study performed at 28 hospitals under the Ministry of Health, Malaysia, involved in the National Surveillance of Multidrug-Resistant Organism, which surveys 6 MDROs (Acinetobacter baumanii, extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli, extended-spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae, carbapenem-resistant Entrobacterales (CRE), methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE)). Results In terms of mortality, 9.6% (n = 951) of the patients died overall, whereas 90.4% (n = 8931) of the patients survived. Healthcare-acquired infection (HCAI) poses a high risk of mortality, with an adjusted odds ratio (aOR) of 2.91 (95% CI: 2.15–3.94). The presence of sterile specimens was significantly associated with increased mortality risk (aOR: 2.33, 95% CI: 2.02–2.68). Gram-negative bacteria had a greater mortality risk (aOR 1.63 95% CI: 1.37–1.93), whereas Acinetobacter baumanii had the highest prevalence of 30.7% (3033) among the 6 MDRO organisms isolated. Patients in medical-based departments had a greater mortality risk (aOR: 1.47, 95% CI: 1.22–1.75). Conclusion HCAIs, Gram-negative bacteria, sterile specimens, medical-based departments and state hospitals have been shown to be associated with increased mortality risk in patients with MDRO infections. Improved surveillance and reporting mechanisms are necessary to better understand the burden of MDRO infections and guide research funding allocation.